The impact of physical exercise on esports players: a monitoring perspective - Kusan, Muhammet; Başoğlu, Burhan; Aydoğmuş, Mert; Ermiş, Sermin Ağralı; Sekban, Gülşah; Bayraktar, Mustafa Tolga; Durmuşoğlu, Mehmet Vakıf; Arslanoğlu, Erkal; Öz, Faik; Ceylan, Levent; Küçük, Hamza; Şahin, Fatma Neşe (Frontiers in Public Health, 2025)
BackgroundEsports has been defined as an organized and competitive approach to playing computer games. The esports industry has grown significantly and continues to develop in recent years. Within this period, monitoring and promoting physical exercise participation among esports players is important. The main aim of this study is to examine esports players’ participation in physical exercise. Another aim is to investigate the impact of physical exercise on body appreciation among esports players.MethodThe study involved 183 esports players (age mean: 23.26; SD: 4.30; n = 42 female, n = 141 male). Data were collected using the Personal Information Form, the International Physical Activity Questionnaire Short Form (IPAQ), and the Body Appreciation Scale.ResultsThe analysis revealed significant differences in total physical activity and body appreciation scores and their sub-dimensions based on income level and years of esports licensing. Demographic factors such as gender, income level, and duration of esports participation were found to have notable effects on physical activity and body appreciation.DiscussionMale players had higher physical activity levels and body appreciation scores than females, and individuals with higher incomes reported better body appreciation. However, an increase in the duration of esports participation led to a decrease in physical activity levels and body appreciation scores. Increasing esports players’ participation in physical activity and promoting physical exercise are recommended.